Stability Enhancement Method of Standalone Modular Multilevel Converters Based on Impedance Reshaping - Zheng, Youzhuo; Hua, Long; Yang, Yekui; Li, Chun; Luo, Chaoyi; Song, Zihong; Yang, Xingwu; Feng, Haibo (Energies (Basel), 2024)
Modular multilevel converters (MMCs) are susceptible to subsynchronous oscillations (SSOs) caused by impedance interactions in the power line. Current research into the stability of MMCs focuses mainly on voltage feed-forward control, while the effect of current feed-forward control is neglected. This paper proposes a current feed-forward compensation method based on impedance reshaping for standalone MMCs. Initially, an impedance model was developed to identify the stability risks caused by the interaction between the MMC and power line impedance. The proposed method feeds the current compensation signal into the modulation circuit, thereby improving the control signal and suppressing the impedance interaction between the MMC and the power line. The analysis of the harmonic state space (HSS) method verifies that the proposed approach effectively reduces the negative damping region in the frequency band where the SSO is located. Additionally, the impedance frequency scanning method confirms the accuracy of impedance modeling. Using the MATLAB/Simulink platform and StarSim HIL hardware-in-the-loop experimental platform, the SSO phenomenon of the MMC is simulated, and the results show that the proposed method can effectively suppress harmonic currents during SSO, which verifies the accuracy of the stability analysis and the feasibility of the proposed method.